“What About the Salmon?” A Critical Analysis of the Pacific Northwest LNG Project in British Columbia - Beattie, Hillary A. (Journal of Aboriginal Economic Development, 2017)
This paper explores the ecological, social, and political implications of the Pacific Northwest liquefied natural gas (LNG) project, which was approved in September 2016 to be built on Lelu Island, British Columbia. The paper situates this LNG project in Canada's settler colonial history and in recent debates over pipelines in British Columbia. Following a description of the approved project, the paper explores the perspectives of industry leaders, government officials, environmental experts, and First Nation communities. Industry leaders support the development, citing economic growth and a reduction in global carbon emissions as benefits. Governments officials largely agree with industry leaders, stating the project would create jobs. They also argue that the project would have limited environmental impacts. However, environmental experts disagree, stating that the project would increase global carbon emissions and have irreversible damages on the local environment. Finally, First Nation communities are divided: some see the project as an economic opportunity while others believe it will result in environmental degradation. However, despite the range of concerns raised by these actors, significant issues have been overlooked. The paper explores these oversights, which include the fact that 'buried' colonial epistemologies underlie the debate and that Lelu Island is unceded Indigenous territory. Overall, the research presented in this paper suggests that the project should not precede until (all) members of the affected First Nation communities have been properly consulted.